Perbedaan MET dengan MET-KT terhadap Nyeri Myofascial Trigger Point Otot Upper Trapezius - Intan Nugraheni Kusuma; Yoni Rustiana Kusumawati; Sugiono Sugiono (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Continuous neck bowing activity and tends to be static will result in mechanical loads on the neck resulting in pain. Neck pain is one of the causes of myofascial trigger point pain in the upper trapezius muscle. In overcoming these disorders, the interventions that can be given are MET and kinesiotaping. Objectives: To determine the difference in the effect of MET with MET and KT on myofascial trigger point pain of the upper trapezius muscle. Methods: This study used an experimental design with two kelompoks with pre and post test which was carried out in June-July 2024, 6 treatments for 2 weeks at PT Indogarment with 31 subjects. The subject collection technique was randomized by taking a lottery number. kelompok A was given treatment in the form of MET and kelompok B was given MET and KT. Pain measurement using QVAS was carried out at the beginning and end of the study. Results: based on the results of statistical tests before and after treatment, in both kelompoks the results obtained p value = 0.001 (p 0.05) which indicates that in kelompok A and kelompok B there is no difference in effect. Conclusion: giving MET or MET and KT can reduce myofascial trigger point pain in the upper trapezius muscle but there is no difference in effect between the two treatment kelompoks. Keywords: Muscle Energy Technique, Kinesiotapping, Pain, Myofascial Triger Point, Upper Trapezius.